Learners' perceptions of creating a collaborative hypermedia product: an exploratory case study at Mount Pleasant Primary School - du Plessis, André (Rhodes University, Faculty of Education, Department of Education, 2004)
The Ministry of Education (SICTE, 2002) states that the widespread introduction of computers in schools should support Curriculum 2005 and that computer technology is part and parcel of making schools the center of community life. The vision is to establish Smart Schools: schools that are reinvented in terms of teaching-learning practices to prepare learners for the information era (SICTE, 2002). Kafai (1996:71) has found that conventional school assignments rarely give learners the opportunity to spend a great deal of time on complex projects. As a result, many learners have little experience in design: planning, problem solving, researching, dealing with time constraints, modifying expectations and synthesizing everything in a project. Research by Carver, Lehrer, Connell and Erickson (1992); Lehrer, (1993); Lehrer, Erickson and Connell (1994); Kafai (1996); Liu and Hsiao (2002) and Liu (2002) indicates that the design of hypermedia artefacts can assist in providing experience in design. To date, no equivalent research has been conducted in South Africa to ascertain the perceptions of learners regarding the creation of a hypermedia artefact over an extended period of time and whether some of the critical outcomes specified in Curriculum 2005 can be addressed in such a learning-by-design hypermedia project. This study shows that design skills and aspects related to the critical outcomes of Curriculum 2005 can be achieved. Furthermore, it indicates that this kind of project encourages interest, motivation and collaboration. In addition, it suggests that learners experience the role of the teacher as different and prefer such a learning environment. In spite of the positive results, some aspects that need attention for future implementation are suggested.
Keywords: Computer-assisted instruction -- South Africa; Computers -- Study and teaching -- South Africa; Education, Elementary -- Activity programs; Competency-based education -- South Africa; Educational technology -- South Africa